2003
DOI: 10.1007/s00125-003-1074-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of adiponectin to body fat distribution, insulin sensitivity and plasma lipoproteins: evidence for independent roles of age and sex

Abstract: Aims/hypothesis. Increased intra-abdominal fat is associated with insulin resistance and an atherogenic lipoprotein profile. Circulating concentrations of adiponectin, an adipocyte-derived protein, are decreased with insulin resistance. We investigated the relationships between adiponectin and leptin, body fat distribution, insulin sensitivity and lipoproteins. Methods. We measured plasma adiponectin, leptin and lipid concentrations, intra-abdominal and subcutaneous fat areas by CT scan, and insulin sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

149
941
26
57

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,316 publications
(1,199 citation statements)
references
References 77 publications
149
941
26
57
Order By: Relevance
“…Cross-sectional studies have shown adiponectin levels to be associated with insulin sensitivity [41,42]. When we use our baseline data to calculate correlations between insulin sensitivity and adiponectin (results not shown), we see the same associations as in the aforementioned cross-sectional studies.…”
Section: Discussionsupporting
confidence: 64%
“…Cross-sectional studies have shown adiponectin levels to be associated with insulin sensitivity [41,42]. When we use our baseline data to calculate correlations between insulin sensitivity and adiponectin (results not shown), we see the same associations as in the aforementioned cross-sectional studies.…”
Section: Discussionsupporting
confidence: 64%
“…Sexual dimorphism in terms of total systemic adiponectin, with women having higher levels of adiponectin than men, has been reported [10,42,43]. Although this was preserved in CSF [18], such findings were achieved using assay-based measures.…”
Section: Discussionmentioning
confidence: 99%
“…2,24 The strongest associations, however, were seen between adiponectin and triglycerides and HDL-cholesterol (components of the insulin resistance syndrome) and these relationships were independent of adiposity and insulin resistance as has been reported in other studies. [26][27][28]43 The mechanisms by which adiponectin may affect blood lipids are substantially unknown. There is some evidence that such effects may be mediated via reduced hepatic lipase activity, an enzyme which contributes to a lowering of HDL-C concentrations 26 low adiponectin is associated with increased hepatic lipase activity in vivo independent of insulin resistance.…”
Section: Associations Of Adiponectin With Metabolic and Vascular Riskmentioning
confidence: 99%
“…[26][27][28]43 The mechanisms by which adiponectin may affect blood lipids are substantially unknown. There is some evidence that such effects may be mediated via reduced hepatic lipase activity, an enzyme which contributes to a lowering of HDL-C concentrations 26 low adiponectin is associated with increased hepatic lipase activity in vivo independent of insulin resistance. 44 No association was seen between adiponectin and blood pressure, consistent with other population based studies.…”
Section: Associations Of Adiponectin With Metabolic and Vascular Riskmentioning
confidence: 99%
See 1 more Smart Citation